Primary Lung Cancer After Treatment for Breast Cancer - Long Q; Wang Y; Che G (Dove Medical Press, 2021)
Qian Long,* Yan Wang,* Guowei Che Department of Thoracic Surgery, West China Hospital, Sichuan University, Chengdu, Sichuan Province, People's Republic of China*These authors contributed equally to this workCorrespondence: Guowei CheDepartment of Thoracic Surgery, West China Hospital, Sichuan University, Chengdu, Sichuan Province, People's Republic of ChinaEmail cheguoweixw@126.comAbstract: Breast cancer is the most common malignancy in women and the second most common cause of cancer-related death. Due to advances in the diagnosis and treatment technologies for breast cancer, patients with breast cancer are living longer than before, resulting in an increased risk of developing subsequent malignancies, among which lung cancer is the most common. This review presents the current evidence about the risk, influencing factors and prognostic factors of developing primary lung cancer after treatment for breast cancer. The aim is to help clinicians improve their understanding, diagnosis and treatment of lung cancer after breast cancer.Keywords: second lung cancer, breast cancer, review